Functional relevance of in vivo half antibody exchange of an IgG4 therapeutic antibody-drug conjugate - Herbener, Peter; Schönfeld, Kurt; König, Martin; Germer, Matthias; Przyborski, Jude M.; Bernöster, Katrin; Schüttrumpf, Jörg (PLOS ONE, 2018)
An increasing number of monoclonal antibodies and derivatives such as antibody-drug conjugates (ADC) are of the IgG1 and IgG4 isotype with distinct structural and functional properties. In cases where antibody-mediated cytotoxicity is not desired, IgG4 is often used, as its Fc region is relatively poor at inducing antibody-dependent cell-mediated or complement-dependent cytotoxicity. IgG4 ADCs with highly cytotoxic drugs against proliferating target cells but which lack or have diminished antibody effector functions against quiescent cells may have a favorable safety profile compared to IgG1. Another unique property of the IgG4 subclass is the capability to exchange half antibodies in vivo creating randomly bispecific antibodies. To investigate the functional properties of process-derived antibody species, and determine the influence of shuffling on the therapeutic efficacy, several model antibodies on the basis of the anti-CD138 antibody-drug conjugate BT062 (Indatuximab ravtansine) were generated: (I) A wild type nBT062, (II) a stable nBT062 comprising mutations to prevent half-antibody exchange, (III) a half nBT062 lacking covalent binding between two heavy chains and (IV) a stabilized, bispecific nBT062-natalizumab antibody with a second, monovalent specificity against CD49d. All nBT062 model variants were capable of CD138-specific binding and antigen-mediated internalization into cells. Furthermore, all nBT062 models inhibited tumor growth in vitro after conjugation with the maytansinoid DM4. The in vivo effects of the different molecular variants were assessed in the MAXF1322 xenograft model. The bispecific nBT062-natalizumab-DM4 demonstrated the least efficacy and was only moderately active even without the co-administration of a human IgG preparation. Wild type, stable and half nBT062-DM4 models demonstrated great anti-tumor activities. The efficacy of wild type and half nBT062-DM4 was reduced in the presence of IgG, while stable nBT062-DM4 was only marginally influenced. These pre-clinical data demonstrate the advantage of introducing half-antibody exchange-preventing mutations into therapeutic IgG4-based antibody drug-conjugates.
Published: April 19, 2018
Gesehen am 18.12.2019